SuperTIGER galactic cosmic-ray source abundances for the charge interval 16 ⩽ Z ⩽ 56 - N.E. Osborn; N.E. Walsh; Q. Abarr; Y. Akaike; W.R. Binns; R.G. Bose; T.J. Brandt; D.L. Braun; N.W. Cannady; R.M. Crabill; P.F. Dowkontt; S.P. Fitzsimmons; et al. (Advances in Space Research, 2026)

SuperTIGER ultra-heavy galactic cosmic ray atmospheric corrections using Geant4 simulations - N.E. Osborn; Q. Abarr; Y. Akaike; W.R. Binns; R.G. Bose; T.J. Brandt; D.L. Braun; N.W. Cannady; R.M. Crabill; P.F. Dowkontt; S.P. Fitzsimmons; T. Hams; et al. (Advances in Space Research, 2026)

Science opportunities with solar sailing smallsats - Slava G. Turyshev; Darren Garber; Louis D. Friedman; Andreas M. Hein; Nathan Barnes; Konstantin Batygin; Michael E. Brown; Leroy Cronin; Artur R. Davoyan; Amber Dubill; T. Marshall Eubanks; Sarah Gibson; et al. (Planetary and Space Science, 2023)

Comprehensive ECG reference intervals in C57BL/6N substrains provide a generalizable guide for cardiac electrophysiology studies in mice - Manuela A. Oestereicher; Janine M. Wotton; Shinya Ayabe; Ghina Bou About; Tsz Kwan Cheng; Jae-Hoon Choi; Dave Clary; Emily M. Dew; Lahcen Elfertak; Alain Guimond; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Mammalian Genome, 2023)
Reference ranges provide a powerful tool for diagnostic decision-making in clinical medicine and are enormously valuable for understanding normality in pre-clinical scientific research that uses in vivo models. As yet, there are no published reference ranges for electrocardiography (ECG) in the laboratory mouse. The first mouse-specific reference ranges for the assessment of electrical conduction are reported herein generated from an ECG dataset of unprecedented scale. International Mouse Phenotyping Consortium data from over 26,000 conscious or anesthetized C57BL/6N wildtype control mice were stratified by sex and age to develop robust ECG reference ranges. Interesting findings include that heart rate and key elements from the ECG waveform (RR-, PR-, ST-, QT-interval, QT corrected, and QRS complex) demonstrate minimal sexual dimorphism. As expected, anesthesia induces a decrease in heart rate and was shown for both inhalation (isoflurane) and injectable (tribromoethanol) anesthesia. In the absence of pharmacological, environmental, or genetic challenges, we did not observe major age-related ECG changes in C57BL/6N-inbred mice as the differences in the reference ranges of 12-week-old compared to 62-week-old mice were negligible. The generalizability of the C57BL/6N substrain reference ranges was demonstrated by comparison with ECG data from a wide range of non-IMPC studies. The close overlap in data from a wide range of mouse strains suggests that the C57BL/6N-based reference ranges can be used as a robust and comprehensive indicator of normality. We report a unique ECG reference resource of fundamental importance for any experimental study of cardiac function in mice.

Global dissemination of influenza A virus is driven by wild bird migration through arctic and subarctic zones - Jonathon D. Gass; Robert J. Dusek; Jeffrey S. Hall; Gunnar Thor Hallgrimsson; Halldór Pálmar Halldórsson; Solvi Runar Vignisson; Sunna Bjork Ragnarsdottir; Jón Einar Jónsson; Scott Krauss; Sook‐San Wong; Xiu‐Feng Wan; Sadia Akter; et al. (Molecular Ecology, 2023)
Influenza A viruses (IAV) circulate endemically among many wild aquatic bird populations that seasonally migrate between wintering grounds in southern latitudes to breeding ranges along the perimeter of the circumpolar arctic. Arctic and subarctic zones are hypothesized to serve as ecologic drivers of the intercontinental movement and reassortment of IAVs due to high densities of disparate populations of long distance migratory and native bird species present during breeding seasons. Iceland is a staging ground that connects the East Atlantic and North Atlantic American flyways, providing a unique study system for characterizing viral flow between eastern and western hemispheres. Using Bayesian phylodynamic analyses, we sought to evaluate the viral connectivity of Iceland to proximal regions and how inter‐species transmission and reassortment dynamics in this region influence the geographic spread of low and highly pathogenic IAVs. Findings demonstrate that IAV movement in the arctic and subarctic reflects wild bird migration around the perimeter of the circumpolar north, favouring short‐distance flights between proximal regions rather than long distance flights over the polar interior. Iceland connects virus movement between mainland Europe and North America, consistent with the westward migration of wild birds from mainland Europe to Northeastern Canada and Greenland. Though virus diffusion rates were similar among avian taxonomic groups in Iceland, gulls play an outsized role as sinks of IAVs from other avian hosts prior to onward migration. These data identify patterns of virus movement in northern latitudes and inform future surveillance strategies related to seasonal and emergent IAVs with potential public health concern.

Importing genetically altered animals: ensuring quality - M.-C. Birling; M. D. Fray; P. Kasparek; J. Kopkanova; M. Massimi; R. Matteoni; L. Montoliu; L. M. J. Nutter; M. Raspa; J. Rozman; E. J. Ryder; F. Scavizzi; et al. (Mammalian Genome, 2022)
The reproducibility of research using laboratory animals requires reliable management of their quality, in particular of their genetics, health and environment, all of which contribute to their phenotypes. The point at which these biological materials are transferred between researchers is particularly sensitive, as it may result in a loss of integrity of the animals and/or their documentation. Here, we describe the various aspects of laboratory animal quality that should be confirmed when sharing rodent research models. We also discuss how repositories of biological materials support the scientific community to ensure the continuity of the quality of laboratory animals. Both the concept of quality and the role of repositories themselves extend to all exchanges of biological materials and all networks that support the sharing of these reagents.

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Temporal dynamics of root and foliar severity of soybean sudden death syndrome at different inoculum densities - Carlos Gongora-Canul; Forrest W. Nutter; Leonor Frazao S. Leandro (European Journal of Plant Pathology, 2012)